The boy in the striped pajamas - Heyman, David, 1961-; Alison, Rosie; Herman, Mark.; Farmiga, Vera.; Thewlis, David, 1963-; Friend, Rupert; Butterfield, Asa, 1997-; Scanlon, Jack.; Hayman, David, 1950-; Boyne, John, 1971-; Miramax Films; BBC Films; et al. (Burbank, Calif. : Miramax Home Entertainment : distributed by Buena Vista Home Entertainment, 2009)
Set in Poland during World War II, 8-year-old Bruno is bored and restless in his new home. Ignoring his mother, he sets off on an adventure in the woods. Soon he meets a young boy in striped pajamas, and a surprising friendship develops.
Widescreen.
Based on the book "The boy in the striped pajamas" by John Boyne.
Special features: Deleted scenes (with optional commentary by writer/director Mark Herman and author John Boyne); "Friendship beyond the fence" featurette; feature commentary by writer/director Mark Herman and author John Boyne.
Director of photography, Benot̋ Delhomme ; editor, Michael Ellis ; music, James Horner.
Vera Farmiga, David Thewlis, Rupert Friend, Asa Butterfield.
MPAA rating: PG-13; for some mature thematic material involving the Holocaust.
Keywords: Boyne, John, -- 1971- -- Film and video adaptations; Auschwitz (Concentration camp) -- Drama; Boys -- Poland -- Drama; Friendship -- Drama; Fences -- Poland -- Drama; Concentration camps -- Poland -- Drama; World War, 1939-1945 -- Prisoners and prisons -- Drama; Holocaust, Jewish (1939-1945) -- Poland -- Drama; Video recordings for the hearing impaired; Film adaptations; Fiction films; Feature films